Highly dispersed Rh single atoms over graphitic carbon nitride as a robust catalyst for the hydroformylation reaction. Issue 5 (23rd January 2023) - Jurado, Lole; Esvan, Jerome; Luque-Álvarez, Ligia A.; Bobadilla, Luis F.; Odriozola, José A.; Posada-Pérez, Sergio; Poater, Albert; Comas-Vives, Aleix; Axet, M. Rosa
Abstract : Rhodium single-atoms on carbon nitride are robust and efficient catalysts for the hydroformylation of styrene. Experimental analyses and DFT calculations confirm the isolated nature of the Rh atoms on carbon nitride and their robustness as catalysts. Abstract : Rhodium-catalysed hydroformylation, effective tool in bulk and fine-chemical synthesis, predominantly uses soluble metal complexes. For that reason, the metal leaching and the catalyst recycling are still the major drawbacks of this process. Single-atom catalysts have emerged as a powerful tool to combine the advantages of both homogeneous and heterogeneous catalysts. Since using an appropriate support material is key to create stable, finely dispersed, single-atom catalysts, here we show that Rh atoms anchored on graphitic carbon nitride are robust catalysts for the hydroformylation reaction of styrene.